Cultural Management as a Tourist Attraction in Indonesia Beautiful Miniature Park (TMII) - Muhammad Imam Ghazali; Maryetti Maryetti; Sahlan Toro; FX Setiyo Wibowo; Ritasari (The Postgraduate School of Tourism Sahid Polytechnic, 2026)
Purpose: This study has goals to analyze how cultural management is implemented into tourism attraction at Indonesia beautiful miniature park (TMII) and to identify the challenges encountered in the management process. Research methods: This research employs a descriptive qualitative method with data collected through interviews, observations, and documentation. Data analysis applies the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing with verification. Data validation is strengthened through member checking to ensure that the researcher’s interpretation aligns with the information provided by the informants. Results: The findings reveal that cultural management at TMII is implemented in a structured and collaborative manner through regular cultural performances, active involvement of regional pavilions in presenting authentic local traditions, and digital promotion strategies that target younger audiences. Educational programs for students further enhance the role of TMII as both a recreational and learning space. However, the research also identifies key challenges, including limited participation of younger generations, shortage of local cultural performers, and insufficient supporting infrastructure to maximize visitor experiences. Conclusions: TMII needs to further strengthen cultural sustainability by integrating innovation in cultural performances, expanding the use of digital platforms to attract broader audiences, and involving local communities more actively. Enhancing infrastructure, encouraging intergenerational cultural transmission, and fostering broader collaboration with educational and cultural institutions are essential to maintaining TMII’s relevance as a cultural tourism destination. Contributions: This study recommends the importance of a cross-stakeholder collaboration model, especially community involvement as cultural performers.